Characterization of Curcuminoid from Curcuma xanthorrhiza and Its Activity Test as Antioxidant and Antibacterial - Sri Atun; Nurfina Aznam; Retno Arianingrum; Senam Senam; Bian Ihda An Naila; Astuti Lestari; Nur Aini Purnamaningsih (Molekul, 2020)
Curcuminoids are the main component found in many Zingiberaceae family plants. The aim of this study was to characterize curcuminoid and its activity test as an antioxidant and antibacterial. Dryed powder of C. xanthorrhiza (1 kg) was macerated with ethanol for 24 hours at room temperature. Ethanol extract of C. xanthorrhiza was subsequently fractionated with n-hexane and chloroform to take the yellow or orange indicated contain of curcuminoids. Analysis of total phenolic levels was carried out by the Follin-Ciaocalteau method. The isolation of curcuminoid componens from this fraction  was carried out by chromatographic method and the structure elucidation was performed by interpretation of spectroscopic data, including UV, IR, 1H and 13C NMR 1D and 2D. The antioxidant activity test used the DPPH (2,2-diphenylpicrylhydrazyl) method, while the antibacterial activity test used Kirby Bauer test diffusion method. The results showed that the curcuminoid fraction yield was 10.06%  from ethanol extract C. xanthorrhiza. The total phenolic content of curcuminoids fraction was 745.45 ± 18.5 mg galic acid (GA)/g extract. Curcuminoids fraction was isolated a known compound desmethoxycurcumin (1). The content of demethoxycurcumin (1) in curcuminoid fraction is 20.97 %.The antioxidant activity of curcuminoids fraction showed strongest activity with IC50 24.98 µg/ml. Antibacterial activity against of the four pathogenic bacteria showed medium activity. The study suggests that curcuminoids extract from C. xanthorrhiza rhizome have potential compounds could be suitable for antioxidant and the treatment of various infections caused of microbial.